2012
DOI: 10.1186/1756-3305-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the geographical distribution and abundance of the tick Ixodes ricinus during the past 30 years in Sweden

Abstract: BackgroundIxodes ricinus is the main vector in Europe of human-pathogenic Lyme borreliosis (LB) spirochaetes, the tick-borne encephalitis virus (TBEV) and other pathogens of humans and domesticated mammals. The results of a previous 1994 questionnaire, directed at people living in Central and North Sweden (Svealand and Norrland) and aiming to gather information about tick exposure for humans and domestic animals, suggested that Ixodes ricinus ticks had become more widespread in Central Sweden and the southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
315
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(350 citation statements)
references
References 42 publications
(98 reference statements)
18
315
1
6
Order By: Relevance
“…Indeed, data from Europe and North America provide evidence that tick distributions have recently shifted or expanded into higher latitudes and altitudes in parallel with rising temperatures. [26][27][28][29] Although mechanisms other than climate variability and change undoubtedly contribute to these outcomes, 30 the repeated observation of range changes correlated with temperature, in a manner consistent with known physiological constraints, argues strongly for a central role of climate in driving changes in tick distributions at broad geographic scales. [31][32][33] This recognition, and the aforementioned agricultural and public health significance of ticks, underlie a growing interest in tick distribution modeling based on future climate scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, data from Europe and North America provide evidence that tick distributions have recently shifted or expanded into higher latitudes and altitudes in parallel with rising temperatures. [26][27][28][29] Although mechanisms other than climate variability and change undoubtedly contribute to these outcomes, 30 the repeated observation of range changes correlated with temperature, in a manner consistent with known physiological constraints, argues strongly for a central role of climate in driving changes in tick distributions at broad geographic scales. [31][32][33] This recognition, and the aforementioned agricultural and public health significance of ticks, underlie a growing interest in tick distribution modeling based on future climate scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, the geographic range of Ixodes ricinus-the most important vector of tick borne zoonoses (TBZ) in Europe-expanded to previously free areas, including greater latitudes in Northern Europe, as well as greater altitudes in the mountains of Central and Southern Europe (Kirby et al, 2004;Materna et al, 2008;Danielová et al, 2006;Jore et al, 2011;Jaenson et al, 2012;Léger et al, 2012). Immature I. ricinus are commonly found on small rodents, which may play important roles in the transmission of agents of TBZ.…”
Section: Introductionmentioning
confidence: 99%
“…Medlock et al (2013) in his review concluded that increased host abundance leading to enhanced tick reproduction in endemic zones and dispersal of roe deer at higher altitude and latitude are key drivers for change in geographical distribution of I. ricinus ticks in Europe. High reproductive potential of roe deer and the capability for disseminating infected ticks to distant areas, far away from the original endemic area, were behind the spread of TBE to the North of Sweden ( Jaenson et al 2012).…”
Section: Discussionmentioning
confidence: 99%